Cancer incidence and mortality: A cohort study in China, 2008-2013 - Pan, R; Zhu, M; Yu, C; Lv, J; Guo, Y; Bian, Z; Yang, L; Chen, Y; Hu, Z; Chen, Z; Li, L; Shen, H; et al. (Wiley, 2017)
The National Central Cancer Registry of China (NCCR) was the only available source of cancer monitoring in China, even though only about 70% of cancer registration sites were qualified by now. In this study, based on a national large prospective cohort-the China Kadoorie Biobank (CKB), we aimed to provide additional cancer statistics and compare the difference of cancer burden between urban and rural areas of China. A total of 497,693 cancer-free participants aged 35-74 years were recruited and successfully followed up from 2004 to 2013 in 5 urban and 5 rural areas across China. Except for traditional registration systems, the national health insurance system and active follow-up were used to determine new cancer incidents and related deaths. The mortality-to-incidence ratio (MIR) was used to compare the differences of cancer burden between urban and rural areas of China. We found that cancer mortality coincided well between our cohort and NCCR, while the incidence was much higher in our cohort. Based on CKB, we found the MIR of all cancers was 0.54 in rural areas, which was approximately one-third higher than that in urban areas with 0.39. Cancer profiles in urban areas were transiting to Western distributions, which were characterized with high incidences of breast cancer and colorectal cancer; while cancers of the esophagus, liver and cervix uteri were still common in rural areas of China. Our results provide additional cancer statistics of China and demonstrate the differences of cancer burden between urban and rural areas of China.